RIP1-Dependent Programmed Necrosis is Negatively Regulated by Caspases During Hepatic Ischemia-Reperfusion. Issue 1 (July 2015) - Rosentreter, Dirk; Funken, Dominik; Reifart, Jörg; Mende, Konstantin; Rentsch, Markus; Khandoga, Andrej
Abstract : ABSTRACT: Programmed necrosis (necroptosis), a newly discovered form of cell death, is mediated by receptor-interacting protein 1 (RIP1) and plays a pivotal role after myocardial, renal, and cerebral ischemia-reperfusion (I/R). The relevance of necroptosis in the postischemic liver remains, however, unclear. The aim of this study was to analyze the role of programed necrosis during hepatic I/R. C57BL6 mice were subjected to warm hepatic I/R (90 min/240 min). The animals were pretreated with either the RIP1 inhibitor necrostatin-1 (Nec-1, 3.5 μg kg −1 ) or vehicle (Nec-1inactive, 3.5 μg kg −1 ) administered systemically before ischemia. Sham-operated animals served as controls (n = 6 each group). The inflammatory response was evaluated by intravital microscopy. The hepatic transaminases alanine aminotransferase/aspartate aminotransferase in plasma as well as the activity of caspase-3 in tissue were determined as markers of hepatocellular injury. Leukocyte recruitment to the liver, sinusoidal perfusion failure, as well as the transaminase activities were strongly increased on I/R as compared with the sham-operated mice. Inhibition of the RIP1-dependent pathway with Nec-1, however, did not attenuate I/R-induced leukocyte migration, perfusion failure, and hepatocellular injury. Western blot analysis showed a baseline RIP1 expression in livers from sham-operated mice, whereas RIP1 expression was not detectable in both Nec-1–treated and vehicle-treated I/R group. Caspase-3 activity was significantly elevated after I/R in both postischemic groups. Our in vivo data show that RIP1-mediated necroptosis is not present in the postischemic liver and that I/R-induced caspase activation is associated with loss of RIP1 expression. Because caspases are able to cleave RIP1, we hypothesize that I/R-triggered caspase activation negatively regulates necroptosis and, thereby, determines apoptosis as a preferred route of cell death after hepatic I/R. Abstract : Supplemental digital content is available in the text.